2021
DOI: 10.1002/adfm.202103347
|View full text |Cite
|
Sign up to set email alerts
|

Bioinert, Stealth or Interactive: How Surface Chemistry of Nanocarriers Determines Their Fate In Vivo

Abstract: Nanocarriers (NCs) have emerged as powerful tools to improve drug solubility, to promote drug transport across membranes, to protect their payload from premature degradation, and to deliver drugs in a controlled and targeted manner. Their performance strongly depends on the surface chemistry, which governs their interaction with the biological environment. Bioinert and stealth surface features are advantageous to avoid unintended interactions with endogenous surfaces at off‐target sites and with the immune sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 382 publications
0
37
0
Order By: Relevance
“…[ 17 ] Finding the balance between antifouling and adsorption of favorable components to prolong blood circulation times, combined with the need to then enable interactions once at the target site, are key challenges in the field. [ 18 ] Among the few existing polymersome studies, many of the trends observed for other nanoparticle systems have been confirmed. Even small changes, for example, in polymer chemical nature or length (degree of polymerization, DP ), can dramatically change antifouling behavior, which can have either a detrimental or beneficial impact on polymersome properties.…”
Section: Introductionmentioning
confidence: 85%
“…[ 17 ] Finding the balance between antifouling and adsorption of favorable components to prolong blood circulation times, combined with the need to then enable interactions once at the target site, are key challenges in the field. [ 18 ] Among the few existing polymersome studies, many of the trends observed for other nanoparticle systems have been confirmed. Even small changes, for example, in polymer chemical nature or length (degree of polymerization, DP ), can dramatically change antifouling behavior, which can have either a detrimental or beneficial impact on polymersome properties.…”
Section: Introductionmentioning
confidence: 85%
“…Under different pH conditions, the amino and carboxyl groups on the NPs would be protonated and deprotonated in a pH‐dependent manner. [ 29 ] Compared with those of −24.38/6.28 mV at the NH 2 /COOH ratio of 10/1, the zeta potentials at pH 7.4 and pH 5.5 were more symmetrical when the NH 2 /COOH ratio was 20/1, which was used in the subsequent investigation. In addition, after 24 h of incubation in cell culture media, the hydrodynamic sizes (Figure 3b) and zeta potentials (Figure 3c) showed no significant changes, indicating sufficient colloidal and chemical grafting stability.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, not only the size and morphology of the MCs must be optimized for safe circulation within vessels, but also the systems' stability has to be maximized to reach both long circulation time and reduced risk of releasing unsafe degradation products into the circulation. Stealthy designs can dramatically extend the circulation time while masking the carriers from clearance cell effectors and protecting them from excretion [416,417]. At the same time, successful intravascular guidance of the MCs must win the forces generated by the hemodynamics [418].…”
Section: Perspectivesmentioning
confidence: 99%